Submerged arc welding sintered flux, its preparation method, welding method and welding material composition

CN122956148APending Publication Date: 2026-10-23JIANGSU RUISEN ZHUOKE NEW MATERIAL TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611451255.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

为解决这一问题,行业内曾尝试在焊剂中单独添加稀土氧化物,以细化焊缝组织,但稀土氧化物的加入方式及与渣系结构的匹配关系尚未明确,实际效果参差不齐

Benefits of technology

1、采用本发明焊剂配合低合金钢焊丝进行埋弧焊接,电弧稳定,焊道表面鱼鳞纹均匀,无咬边、气孔等表面缺陷;渣壳在冷却后可自行翘起或轻敲脱落,焊后清理方便。所述焊剂按国际焊接学会BⅡw公式计算的碱度为2.1-3.0,其中:当碱度低于2.1时,熔渣中SiO2比例相对升高,导致熔渣结构偏向硅酸盐网络结构,流动性虽提高,但脱硫脱磷能力下降;当碱度高于3.0时,MgO、CaF2比例过高,熔渣粘度明显增加,渣壳与焊缝表面结合增强,脱渣困难;当碱度处于2.1-3.0范围内时,熔渣在具备足够流动性的同时保持较好的脱硫脱磷能力,从而兼顾焊缝纯净度与脱渣性能。所述Fe-Si合金粉在焊接过程中参与熔池冶金反应,起到辅助脱氧作用,并与稀土氧化物协同影响夹杂物形态。所述稀土氧化物在焊接过程中与氧、硫等元素形成高熔点复合夹杂物,促进夹杂物由长条状向细小弥散颗粒转变,从而降低应力集中,提高熔敷金属低温冲击韧性。但该改善作用依赖于渣系碱度环境,当碱度偏离2.1-3.0范围时,稀土氧化物对冲击韧性的提升幅度减弱。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956148A_ABST
    Figure CN122956148A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of welding materials, and particularly relates to a sintered flux for submerged arc welding, a preparation method, a welding method and a welding material composition. The sintered flux for submerged arc welding is prepared by mixing dry powder raw materials with a binder, granulating, drying and sintering. The dry powder raw materials are composed of CaF2: 22%-28%, MgO: 26%-32%, Al2O3: 18%-24%, SiO2: 8%-12%, CaO: 3%-7%, MnO: 2%-5%, TiO2: 1%-3%, rare earth oxide 0.5%-2% and Fe-Si alloy powder 1%-3% by mass percentage. The binder is a mixed water glass of potassium and sodium, and the addition amount is 15%-20% of the total mass of the dry powder raw materials. The basicity BIIw is 2.1-3.0. When the flux is used for submerged arc welding with low alloy steel welding wire, the weld surface is smooth and the average impact energy of the deposited metal at -40 DEG C is above 76 J.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of welding materials technology, specifically relating to a sintered flux for submerged arc welding, its preparation method, welding method, and welding material composition. Background Technology

[0002] Submerged arc welding (SAW) is widely used in the manufacture of large steel structures such as pressure vessels, offshore platforms, pipeline steel pipes, and wind turbine towers. During welding, the flux covers the electric arc and the molten pool, serving both to isolate the weld from the air and participating in the metallurgical reaction. Its composition directly affects the chemical composition and mechanical properties of the weld metal. Based on manufacturing methods, SAW fluxes are classified into two types: smelted fluxes and sintered fluxes. Sintered fluxes do not require smelting; they are produced by mixing dry powder raw materials with a binder, granulating, drying, and sintering. The formulation is relatively flexible, and their industrial use is increasing year by year.

[0003] Fluoroalkali slag systems, primarily composed of calcium fluoride, magnesium oxide, aluminum oxide, silicon dioxide, and calcium oxide, are a commonly used type of slag system in sintered welding fluxes. Currently, the most common sintered welding fluxes in this system typically have a silicon dioxide content of over 15% and a magnesium oxide content usually not exceeding 25%. When used with low-alloy steel welding wire in submerged arc welding, this type of flux provides stable arc combustion and relatively easy slag removal. However, several problems have also emerged in practical engineering applications, mainly manifested in the following three aspects: 1. Insufficient stability of low-temperature impact toughness in weld metal. Impact energy data of deposited metal obtained from the same batch of flux under different welding conditions may fluctuate significantly. For welded structures required to operate at -40℃ or lower, this fluctuation introduces uncertainty into engineering quality control. To address this issue, the industry has attempted to add rare earth oxides separately to the flux to refine the weld microstructure. However, the method of adding rare earth oxides and their compatibility with the slag structure are not yet clear, resulting in inconsistent practical effects.

[0004] 2. Balancing slag removal performance and weld purity is challenging. To reduce the diffusible hydrogen content in the weld metal or improve strength, it is often necessary to increase the flux basicity or the proportion of calcium fluoride. However, such adjustments can easily lead to increased slag viscosity and difficulty in post-weld slag removal. Conversely, reducing basicity or decreasing components such as alumina and magnesium oxide to improve slag removal performance may weaken the flux's desulfurization and dephosphorization capabilities, increasing the content of sulfur, phosphorus, and other impurities in the weld. When basicity deviates from the suitable range, this contradiction manifests as follows: too low basicity results in insufficient purity, while too high basicity worsens slag removal, and further increasing basicity does not further improve impact toughness. The definition of this suitable range is not yet clear in the existing technology.

[0005] 3. Physical quality of flux particles. Some sintered fluxes have low particle strength after sintering and absorb moisture quickly, making them prone to pulverization or clumping during storage or transportation. This affects the normal feeding of flux into the hopper, leading to unstable arcs or poor weld formation. The industry has attempted to improve particle strength by adjusting the binder ratio or changing the sintering process, but both binder dosage and sintering temperature have process window limitations; temperatures below or above these windows will result in a decrease in particle quality.

[0006] Since the above three issues belong to different technical levels, the existing technology often fails to address all aspects by adjusting a single factor, and has not yet formed a comprehensive solution that can simultaneously take into account low-temperature impact toughness stability, slag removal performance and weld purity, as well as the physical quality of flux particles. Summary of the Invention

[0007] The purpose of this invention is to provide a sintered flux for submerged arc welding, its preparation method, welding method, and welding material composition.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A sintered flux for submerged arc welding is produced by mixing dry powder raw materials and a binder, followed by granulation, drying, and sintering. The dry powder raw materials are composed of the following components by mass percentage: CaF2: 22%-28%; MgO: 26%-32%; Al2O3: 18%-24%; SiO2: 8%-12%; CaO: 3%-7%; MnO: 2%-5%; TiO2: 1%-3%; Rare earth oxides: 0.5%-2%; Fe-Si alloy powder: 1%-3%; The remainder are unavoidable impurities; these impurities originate from the aforementioned industrial raw materials and do not participate in the functional design of the flux. The binder is a potassium-sodium mixed water glass, and the amount added is 15%-20% of the total mass of the dry powder raw materials. The flux contains ≤0.030% S by mass and ≤0.030% P by mass. The basicity of the flux, calculated according to the International Institute of Welding (IIW) formula, is 2.1-3.0.

[0009] Furthermore, the dry powder raw material is composed of the following components by mass percentage: CaF2: 24%-26%; MgO: 28%-30%; Al2O3: 20%-22%; SiO2: 9%-11%; CaO: 4%-6%; MnO: 3%-4%; TiO2: 1.5%-2.5%; Rare earth oxides: 1%-1.5%; Fe-Si alloy powder: 1.5%-2.5%.

[0010] Furthermore, the rare earth oxide is cerium oxide and / or lanthanum oxide.

[0011] Furthermore, the purity of CaF2 is ≥97%, S≤0.02%, and P≤0.02%; the purity of MgO is ≥95%; and the purity of Al2O3 is ≥85%.

[0012] Furthermore, the mass ratio of K2O to Na2O in the potassium-sodium mixed water glass is 1.5:1-2.5:1, the modulus is 2.5-3.2, and the Baume degree is 38°Bé-45°Bé.

[0013] Furthermore, the basicity of the flux, calculated according to the International Institute of Welding (IIW) formula, is 2.5-3.0.

[0014] A method for preparing a sintered flux for submerged arc welding includes the following steps: Step 1, Ingredients: Weigh each component according to the mass percentage of the above-mentioned dry powder raw materials; Step 2, Dry mixing: Add the weighed dry powder raw materials into the mixing equipment and stir for 15-30 minutes; Step 3, wet mixing: Add the binder to the dry powder material and continue stirring and mixing for 10-20 minutes to obtain a wet material; Step 4, Granulation: The wet material is fed into the granulation equipment to produce granules with a particle size of 0.45mm-2.5mm; Step 5, Drying: Dry the granulated particles at 180℃-220℃ for 60min-90min; Step 6, Sintering: Sinter the dried particles at 750℃-850℃ for 60min-120min; Step 7, sieving: The sintered particles are sieved, and particles with a size of 0.45mm-2.5mm are obtained to obtain the sintered flux for submerged arc welding.

[0015] Furthermore, in step 6, the sintering temperature is 780℃-820℃ and the sintering time is 80min-100min; after sieving in step 7, the mass percentage of fine particles with a particle size less than 0.45mm in the obtained flux is no more than 5%, and the mass percentage of coarse particles with a particle size greater than 2.5mm is no more than 2%.

[0016] A submerged arc welding method, using the aforementioned sintered flux for submerged arc welding, in conjunction with low alloy steel welding wire, to perform submerged arc welding on the workpiece to be welded.

[0017] A submerged arc welding material composition includes the aforementioned sintered flux for submerged arc welding and a low-alloy steel welding wire matched with the flux.

[0018] Beneficial effects of this invention: 1. Submerged arc welding using the flux of this invention in conjunction with low-alloy steel welding wire results in a stable arc, uniform fish-scale pattern on the weld surface, and absence of surface defects such as undercut and porosity. The slag shell can be lifted off by itself or gently tapped off after cooling, facilitating post-weld cleaning. The flux has a basicity of 2.1-3.0 calculated according to the International Institute of Welding (IIW) formula. Specifically: when the basicity is below 2.1, the proportion of SiO2 in the slag increases relatively, leading to a slag structure that leans towards a silicate network structure. While this improves fluidity, it reduces desulfurization and dephosphorization capabilities. When the basicity is above 3.0, the proportions of MgO and CaF2 are too high, significantly increasing slag viscosity and strengthening the bond between the slag shell and the weld surface, making slag removal difficult. When the basicity is within the range of 2.1-3.0, the slag maintains good desulfurization and dephosphorization capabilities while possessing sufficient fluidity, thus balancing weld purity and slag removal performance. The Fe-Si alloy powder participates in the metallurgical reaction of the molten pool during welding, playing an auxiliary deoxidation role and synergistically influencing the morphology of inclusions with rare earth oxides. During welding, the rare earth oxides form high-melting-point composite inclusions with elements such as oxygen and sulfur, promoting the transformation of these inclusions from elongated shapes to fine, dispersed particles. This reduces stress concentration and improves the low-temperature impact toughness of the weld metal. However, this improvement depends on the alkalinity of the slag environment; when the alkalinity deviates from the range of 2.1-3.0, the improvement in impact toughness by rare earth oxides weakens.

[0019] 2. After adding 0.5%-2% rare earth oxides, the average impact energy of the weld metal at -40℃ was significantly higher than that of the control group without rare earth oxides. The fluctuations between the test values ​​of each impact sample were small, and the stability of the low-temperature impact toughness was improved. At the same time, the yield strength, tensile strength, and elongation after fracture of the weld metal all met the relevant standard requirements for welding low-alloy high-strength steel.

[0020] 3. Using potassium-sodium mixed water glass as a binder, with an addition amount of 15%-20% and a sintering temperature of 750℃-850℃, the resulting flux particles have high strength, show no obvious clumping or powdering after three months of storage, maintain good fluidity in the flux hopper, and are evenly fed during the welding process.

[0021] 4. The flux contains ≤0.030% sulfur and ≤0.030% phosphorus. By selecting high-purity raw materials, the amount of harmful elements introduced is further controlled, reducing the adverse effects of sulfur and phosphorus in the weld metal.

[0022] 5. This invention integrates three different aspects of the problem—low-temperature impact toughness, slag removal performance, and physical quality of flux particles—into a unified solution through the coordinated design of dry powder raw material composition ratio, binder parameters, and sintering process. This avoids the problem of neglecting one aspect for another caused by adjusting a single factor in the prior art. It is suitable for submerged arc welding of low-alloy high-strength steel with high requirements for low-temperature impact toughness. Attached Figure Description

[0023] Figure 1 This is a process flow diagram for preparing the sintered flux for submerged arc welding according to the present invention. Detailed Implementation

[0024] The present invention will be further described in detail below with reference to embodiments and comparative examples. It should be understood that these embodiments are only used to explain the content of the present invention and do not constitute any limitation on the scope of protection of the present invention. Simple modifications or equivalent substitutions made based on the concept of the present invention are all within the scope of protection of the present invention.

[0025] Raw material description The sources and specifications of the dry powder raw materials used in the following examples and comparative examples are as follows: Fluorite: CaF2 content 97.5%, S≤0.015%, P≤0.018%, particle size ≤5% residue on 200 mesh sieve; Fused magnesia: MgO content 96.0%, SiO2≤1.2%, CaO≤1.5%, Fe2O3≤0.8%, particle size ≤5% residue on 200 mesh sieve; Sintered magnesia: MgO content 94.0%, SiO2 ≤ 2.5%, CaO ≤ 2.0%, particle size ≤ 5% residue on 200 mesh sieve; Bauxite: Al2O3 content 86.0%, SiO2≤7.0%, Fe2O3≤2.0%, particle size ≤5% residue on 200 mesh sieve; Calcined alumina: Al2O3 content 99.0%, particle size ≤5% residue on 325 mesh sieve; Quartz sand: SiO2 content 98.5%, particle size ≤5% residue on 200 mesh sieve; Limestone: After calcination at 1000℃ for 2 hours, CaO content is 95.0%, and the residue on a 200-mesh sieve is ≤5%. Manganese ore: MnO content 82.0%, particle size ≤5% residue on 200 mesh sieve; Titanium dioxide: TiO2 content 98.0%, particle size ≤5% residue on 325 mesh sieve; Cerium oxide: CeO2 content 99.0%, particle size ≤3% residue on 400 mesh sieve; Lanthanum oxide: La2O3 content 99.0%, particle size ≤3% residue on 400 mesh sieve; Fe-Si alloy powder: Si content 45%, balance is Fe and unavoidable impurities, particle size ≤5% on 100 mesh sieve; Potassium-sodium mixed water glass: K2O to Na2O mass ratio 2:1, modulus 2.8, Baumé degree 40°Bé.

[0026] Of the above raw materials, fluorite, fused magnesia / sintered magnesia, bauxite / calcined alumina, quartz sand, limestone, manganese ore, titanium dioxide, and Fe-Si alloy powder are all commercially available products commonly used in the welding materials industry, while cerium oxide and lanthanum oxide are commercially available industrial-grade rare earth oxides. All raw materials were dried at 110℃ for 2 hours before use to remove free moisture. Example 1

[0027] Weigh the following dry powder raw materials by weight percentage: 27.0 kg fluorite (CaF2 content 97.5%, equivalent to 26.33 kg pure CaF2), 30.0 kg fused magnesia (MgO content 96.0%, equivalent to 28.80 kg pure MgO), 19.0 kg bauxite (Al2O3 content 86.0%, equivalent to 16.34 kg pure Al2O3, MgO content 0.6%, equivalent to 0.11 kg pure MgO), 5.0 kg calcined alumina (Al2O3 content 99.0%, equivalent to 4.95 kg pure Al2O3), and 10.0 kg quartz sand (SiO2 content 98.0%). The total dry powder raw materials are: 105.2 kg (containing 9.5% CaO, equivalent to 9.85 kg of pure SiO2), 4.0 kg of calcined limestone (containing 95.0% CaO, equivalent to 3.80 kg of pure CaO), 3.5 kg of manganese ore (containing 82.0% MnO, equivalent to 2.87 kg of pure MnO), 1.5 kg of titanium dioxide (containing 98.0% TiO2, equivalent to 1.47 kg of pure TiO2), 1.0 kg of cerium oxide (containing 99.0% CeO2, equivalent to 0.99 kg of pure CeO2), and 2.0 kg of Fe-Si alloy powder (containing 45% Si, with the balance being Fe and unavoidable impurities). The unavoidable impurities in the raw materials total approximately 1.8 kg, which are derived from industrial raw materials and do not participate in the functional design of the flux. Including impurities, the total mass of the dry powder system is 103.0 kg.

[0028] The mass percentage of the finished flux components (with the total mass of 103.0 kg as the denominator) is as follows: CaF2 = 26.33 ÷ 103.0 = 25.6%; MgO = (28.80 + 0.11) ÷ 103.0 = 28.91 ÷ 103.0 = 28.1%; Al2O3 = (16.34 + 4.95) ÷ 103.0 = 21.29 ÷ 103.0 = 20.7%; SiO2 = 9.85 ÷ 103.0 = 9.6%; CaO = 3.80 ÷ 103.0 = 3.7%; MnO = 2.87 ÷ 103.0 = 2.8%; TiO2 = 1.47 ÷ 103.0 = 1.4%; CeO2 = 0.99 ÷ 103.0 = 1.0%; Fe-Si = 2.00 ÷ 103.0 = 1.9%; Impurities (balance) ≈ 5.2%.

[0029] Alkalinity BⅡw calculation: Numerator = CaF2 + MgO + CaO + MnO = 25.6 + 28.1 + 3.7 + 2.8 = 60.2; Denominator = SiO2 + 0.5 × (Al2O3 + TiO2) = 9.6 + 0.5 × (20.7 + 1.4) = 9.6 + 11.05 = 20.65; BⅡw = 60.2 ÷ 20.65 = 2.9.

[0030] The weighed dry powder raw materials were put into a horizontal mixer and stirred for 20 minutes until the material was uniform in color and there was no obvious color difference visible to the naked eye. 18.0 kg of potassium-sodium mixed water glass (K2O to Na2O mass ratio 2:1, modulus 2.8, Baume degree 40°Bé) was added to the uniformly mixed dry powder material, accounting for 17.5% of the total mass of the dry powder raw materials. Stirring and mixing continued for 15 minutes to obtain the wet material.

[0031] Wet material is fed into a rotary granulator for granulation. By adjusting the rotation speed and tilt angle of the granulating disc, the particle size is controlled to be 0.45mm-2.5mm (8-40 mesh). The granulated particles are then sent to an electrically heated blast drying oven and dried at 200℃ for 75 minutes. The dried particles are then sent to a box-type resistance sintering furnace, where the temperature is increased from room temperature to 800℃ at a rate of 5℃ / min, held at that temperature for 90 minutes, and then allowed to cool naturally to room temperature before being discharged. The sintered particles are sieved, and particles with a size of 0.45mm-2.5mm are selected, of which fine particles smaller than 0.45mm account for 3.8% by mass and coarse particles larger than 2.5mm account for 1.2% by mass. This yields the sintered flux for submerged arc welding in this embodiment. Figure 1 ). Example 2

[0032] Weigh the following dry powder raw materials by weight percentage: 26.0 kg of fluorite (CaF2 content 97.5%, equivalent to 25.35 kg of pure CaF2), 31.0 kg of fused magnesia (MgO content 96.0%, equivalent to 29.76 kg of pure MgO), 18.0 kg of bauxite (Al2O3 content 86.0%, equivalent to 15.48 kg of pure Al2O3, MgO content 0.6%, equivalent to 0.11 kg of pure MgO), 5.5 kg of calcined alumina (Al2O3 content 99.0%, equivalent to 5.45 kg of pure Al2O3), and quartz. The following raw materials were added: 9.5 kg of sand (SiO2 content 98.5%, equivalent to 9.36 kg of pure SiO2), 4.0 kg of calcined limestone (CaO content 95.0%, equivalent to 3.80 kg of pure CaO), 4.0 kg of manganese ore (MnO content 82.0%, equivalent to 3.28 kg of pure MnO), 1.5 kg of titanium dioxide (TiO2 content 98.0%, equivalent to 1.47 kg of pure TiO2), 1.2 kg of lanthanum oxide (La2O3 content 99.0%, equivalent to 1.19 kg of pure La2O3), and 2.0 kg of Fe-Si alloy powder. The total dry powder input was 102.7 kg. The unavoidable total impurities in the raw materials were approximately 1.8 kg. Including impurities, the total mass of the dry powder system was 102.7 kg.

[0033] The mass percentage of the finished flux components is as follows: CaF2 = 25.35 ÷ 102.7 = 24.7%; MgO = (29.76 + 0.11) ÷ 102.7 = 29.87 ÷ 102.7 = 29.1%; Al2O3 = (15.48 + 5.45) ÷ 102.7 = 20.93 ÷ 102.7 = 20.4%; SiO2 = 9.36 ÷ 102.7 = 9.1%; CaO = 3.80 ÷ 102.7 = 3.7%; MnO = 3.28 ÷ 102.7 = 3.2%; TiO2 = 1.47 ÷ 102.7 = 1.4%; La2O3 = 1.19 ÷ 102.7 = 1.2%; Fe-Si = 2.00 ÷ 102.7 = 1.9%; Impurities (balance) ≈ 5.3%.

[0034] Alkalinity BⅡw verification: Numerator = 24.7 + 29.1 + 3.7 + 3.2 = 60.7; Denominator = 9.1 + 0.5 × (20.4 + 1.4) = 9.1 + 10.9 = 20.0; BⅡw = 60.7 ÷ 20.0 = 3.0.

[0035] The preparation process is basically the same as in Example 1, except that: the amount of binder added is 18.5 kg, accounting for 18.0% of the total mass of the dry powder raw materials; the drying temperature is 190℃, and the drying time is 85 min; the sintering temperature is 820℃, and the holding time is 85 min. After sieving, the mass ratio of fine particles is 3.5%, and the mass ratio of coarse particles is 1.0%. Example 3

[0036] Weigh the following dry powder raw materials by mass percentage: 24.0 kg of fluorite (CaF2 content 97.5%, equivalent to 23.40 kg of pure CaF2), 30.5 kg of sintered magnesia (MgO content 94.0%, equivalent to 28.67 kg of pure MgO), 22.0 kg of bauxite (Al2O3 content 86.0%, equivalent to 18.92 kg of pure Al2O3, MgO content 0.6%, equivalent to 0.13 kg of pure MgO), and 4.0 kg of calcined alumina (Al2O3 content 99.0%, equivalent to 3.96 kg of pure Al2O3). The raw materials contain 11.5 kg of quartz sand (SiO2 content 98.5%, equivalent to 11.33 kg of pure SiO2), 3.5 kg of calcined limestone (CaO content 95.0%, equivalent to 3.33 kg of pure CaO), 3.5 kg of manganese ore (MnO content 82.0%, equivalent to 2.87 kg of pure MnO), 1.5 kg of titanium dioxide (TiO2 content 98.0%, equivalent to 1.47 kg of pure TiO2), 0.6 kg of cerium oxide (CeO2 content 99.0%, equivalent to 0.59 kg of pure CeO2), and 1.5 kg of Fe-Si alloy powder. The total unavoidable impurities in the raw materials are approximately 1.8 kg. Including impurities, the total mass of the dry powder system is 102.6 kg.

[0037] The mass percentage of the finished flux components is as follows: CaF2 = 23.40 ÷ 102.6 = 22.8%; MgO = (28.67 + 0.13) ÷ 102.6 = 28.80 ÷ 102.6 = 28.1%; Al2O3 = (18.92 + 3.96) ÷ 102.6 = 22.88 ÷ 102.6 = 22.3%; SiO2 = 11.33 ÷ 102.6 = 11.0%; CaO = 3.33 ÷ 102.6 = 3.2%; MnO = 2.87 ÷ 102.6 = 2.8%; TiO2 = 1.47 ÷ 102.6 = 1.4%; CeO2 = 0.59 ÷ 102.6 = 0.6%; Fe-Si = 1.50 ÷ 102.6 = 1.5%; Impurities (balance) ≈ 6.3%.

[0038] Alkalinity BⅡw calculation: Numerator = 22.8 + 28.1 + 3.2 + 2.8 = 56.9; Denominator = 11.0 + 0.5 × (22.3 + 1.4) = 11.0 + 11.85 = 22.85; BⅡw = 56.9 ÷ 22.85 = 2.5.

[0039] The preparation process is basically the same as in Example 1, except that: the amount of binder added is 17.0 kg, accounting for 16.6% of the total mass of the dry powder raw materials; the drying temperature is 210℃, and the drying time is 70 min; the sintering temperature is 780℃, and the holding time is 110 min. After sieving, the mass ratio of fine particles is 4.1%, and the mass ratio of coarse particles is 1.6%. Example 4

[0040] Weigh the following dry powder raw materials according to their mass percentages: 22.56 kg of fluorite (CaF2 content 97.5%, equivalent to 22.0 kg of pure CaF2), 27.08 kg of fused magnesia (MgO content 96.0%, equivalent to 26.0 kg of pure MgO), 27.91 kg of bauxite (Al2O3 content 86.0%, equivalent to 24.0 kg of pure Al2O3), 12.18 kg of quartz sand (SiO2 content 98.5%, equivalent to 12.0 kg of pure SiO2), and 3.16 kg of calcined limestone. The raw materials consist of: (CaO content 95.0%, equivalent to 3.0 kg of pure CaO), 2.44 kg of manganese ore (MnO content 82.0%, equivalent to 2.0 kg of pure MnO), 3.06 kg of titanium dioxide (TiO2 content 98.0%, equivalent to 3.0 kg of pure TiO2), 0.51 kg of cerium oxide (CeO2 content 99.0%, equivalent to 0.5 kg of pure CeO2), and 1.0 kg of Fe-Si alloy powder (Si content 45%, balance being Fe and unavoidable impurities), totaling 99.90 kg of dry powder raw materials. The total unavoidable impurities in the raw materials amount to approximately 6.72 kg. After including impurities, the total mass of the dry powder system is 99.90 kg.

[0041] The mass percentage of the finished flux components (with the total mass of 99.90 kg as the denominator) is as follows: CaF2=22.0%; MgO=26.0%; Al2O3=24.0%; SiO2=12.0%; CaO=3.0%; MnO=2.0%; TiO2=3.0%; CeO2=0.5%; Fe-Si=1.0%; impurities (balance) ≈ 6.7%.

[0042] Alkalinity BⅡw calculation: Numerator = CaF2 + MgO + CaO + MnO = 22.0 + 26.0 + 3.0 + 2.0 = 53.0; Denominator = SiO2 + 0.5 × (Al2O3 + TiO2) = 12.0 + 0.5 × (24.0 + 3.0) = 25.5; BⅡw = 53.0 ÷ 25.5 ≈ 2.08.

[0043] Weigh the dry powder raw materials and put them into a horizontal mixer. Stir and mix for 15 minutes until the material is uniform in color. Add 15 kg of potassium sodium mixed water glass to the uniformly mixed dry powder material, accounting for 15% of the total mass of the dry powder raw materials, and continue to stir and mix for 10 minutes to obtain the wet material.

[0044] The wet material is fed into a rotary granulator for granulation, controlling the particle size to be 0.45mm-2.5mm. The granulated particles are then sent to an electrically heated blast drying oven and dried at 180℃ for 60 minutes. The dried particles are then sent to a box-type resistance sintering furnace, where the temperature is increased from room temperature to 750℃ at a rate of 5℃ / min, held at that temperature for 120 minutes, and then allowed to cool naturally to room temperature before being discharged. The sintered particles are sieved, and particles with a size of 0.45mm-2.5mm are selected, wherein fine particles smaller than 0.45mm account for 4.5% of the mass, and coarse particles larger than 2.5mm account for 1.8% of the mass, thus obtaining the sintered flux for submerged arc welding in this embodiment. Example 5

[0045] Weigh the following dry powder raw materials by mass percentage: 28.21 kg fluorite (CaF2 content 97.5%, equivalent to 27.5 kg pure CaF2), 32.81 kg fused magnesia (MgO content 96.0%, equivalent to 31.5 kg pure MgO), 20.93 kg bauxite (Al2O3 content 86.0%, equivalent to 18.0 kg pure Al2O3), 12.18 kg quartz sand (SiO2 content 98.5%, equivalent to 12.0 kg pure SiO2), and 3.16 kg calcined limestone (C... The raw materials consist of: 95.0% CaO (equivalent to 3.0 kg of pure CaO), 2.44 kg of manganese ore (82.0% MnO (equivalent to 2.0 kg of pure MnO)), 1.02 kg of titanium dioxide (98.0% TiO2 (equivalent to 1.0 kg of pure TiO2)), 2.02 kg of lanthanum oxide (99.0% La2O3 (equivalent to 2.0 kg of pure La2O3)), and 3.0 kg of Fe-Si alloy powder (45% Si, with the remainder being Fe and unavoidable impurities), totaling 105.77 kg of dry powder. The total unavoidable impurities in the raw materials are approximately 9.89 kg. Including impurities, the total mass of the dry powder system is 105.77 kg.

[0046] The mass percentage of the finished flux components (with the total mass of 105.77 kg as the denominator) is as follows: CaF2=27.5%; MgO=31.5%; Al2O3=18.0%; SiO2=12.0%; CaO=3.0%; MnO=2.0%; TiO2=1.0%; La2O3=2.0%; Fe-Si=3.0%; impurities (balance) ≈ 9.4%.

[0047] Alkalinity BⅡw calculation: Numerator = CaF2 + MgO + CaO + MnO = 27.5 + 31.5 + 3.0 + 2.0 = 64.0; Denominator = SiO2 + 0.5 × (Al2O3 + TiO2) = 12.0 + 0.5 × (18.0 + 1.0) = 21.5; BⅡw = 64.0 ÷ 21.5 ≈ 2.98.

[0048] Weigh the dry powder raw materials and put them into a horizontal mixer. Stir and mix for 30 minutes until the material is uniform in color. Add 21.15 kg of potassium-sodium mixed water glass to the uniformly mixed dry powder material, accounting for 20% of the total mass of the dry powder raw materials, and continue stirring and mixing for 20 minutes to obtain the wet material.

[0049] The wet material is fed into a rotary granulator for granulation, controlling the particle size to be 0.45mm-2.5mm. The granulated particles are then fed into an electrically heated blast drying oven and dried at 220℃ for 90 minutes. The dried particles are then fed into a box-type resistance sintering furnace, where the temperature is increased from room temperature to 850℃ at a rate of 5℃ / min, held at that temperature for 60 minutes, and then allowed to cool naturally to room temperature before being discharged. The sintered particles are sieved, and particles with a size of 0.45mm-2.5mm are selected, wherein fine particles smaller than 0.45mm account for 4.2% of the mass, and coarse particles larger than 2.5mm account for 1.7% of the mass, thus obtaining the sintered flux for submerged arc welding in this embodiment.

[0050] Comparative Example 1 Rare earth oxides were not added to the dry powder raw material, and the remaining components and contents were basically the same as in Example 1.

[0051] Weigh the following dry powder raw materials: 27.0 kg fluorite (equivalent to 26.33 kg pure CaF2), 30.0 kg fused magnesia (equivalent to 8.80 kg pure MgO), 19.0 kg bauxite (equivalent to 16.34 kg pure Al2O3 and 0.11 kg pure MgO), 5.0 kg calcined alumina (equivalent to 4.95 kg pure Al2O3), 10.0 kg quartz sand (equivalent to 9.85 kg pure SiO2), 4.0 kg calcined limestone (equivalent to 3.80 kg pure CaO), 3.5 kg manganese ore (equivalent to 2.87 kg pure MnO), 1.5 kg titanium dioxide (equivalent to 1.47 kg pure TiO2), and 2.0 kg Fe-Si alloy powder. The total dry powder input is approximately 102.0 kg. The basicity of the finished flux is BⅡw = 2.9.

[0052] The preparation process is the same as in Example 1. After sieving, the mass percentage of fine particles is 3.6%, and the mass percentage of coarse particles is 1.1%.

[0053] Comparative Example 2 Weigh the following dry powder raw materials: 22.0 kg of fluorite (equivalent to 21.45 kg of pure CaF2), 25.0 kg of fused magnesia (equivalent to 24.00 kg of pure MgO), 20.0 kg of bauxite (equivalent to 17.20 kg of pure Al2O3 and 0.12 kg of pure MgO), 3.0 kg of calcined alumina (equivalent to 2.97 kg of pure Al2O3), 16.0 kg of quartz sand (equivalent to 15.76 kg of pure SiO2), 3.0 kg of calcined limestone (equivalent to 2.85 kg of pure CaO), 3.0 kg of manganese ore (equivalent to 2.46 kg of pure MnO), 1.5 kg of titanium dioxide (equivalent to 1.47 kg of pure TiO2), 1.0 kg of cerium oxide (equivalent to 0.99 kg of pure CeO2), and 2.0 kg of Fe-Si alloy powder. The total dry powder input is 96.5 kg. The total unavoidable impurities in the raw materials amount to approximately 1.7 kg. After accounting for impurities, the total mass of the dry powder system is 96.5 kg.

[0054] The mass percentage of the finished flux components is as follows: CaF2 = 21.45 ÷ 96.5 = 22.2%; MgO = (24.00 + 0.12) ÷ 96.5 = 24.12 ÷ 96.5 = 25.0%; Al2O3 = (17.20 + 2.97) ÷ 96.5 = 20.17 ÷ 96.5 = 20.9%; SiO2 = 15.76 ÷ 96.5 = 16.3%; CaO = 2.85 ÷ 96.5 = 3.0%; MnO = 2.46 ÷ 96.5 = 2.5%; TiO2 = 1.47 ÷ 96.5 = 1.5%; CeO2 = 0.99 ÷ 96.5 = 1.0%; Fe-Si = 2.00 ÷ 96.5 = 2.1%; Impurities (balance) ≈ 5.5%.

[0055] Alkalinity BⅡw calculation: Numerator = 22.2 + 25.0 + 3.0 + 2.5 = 52.7; Denominator = 16.3 + 0.5 × (20.9 + 1.5) = 16.3 + 11.2 = 27.5; BⅡw = 52.7 ÷ 27.5 = 1.9.

[0056] The preparation process is the same as in Example 1. After sieving, the mass percentage of fine particles is 3.7%, and the mass percentage of coarse particles is 1.3%.

[0057] Comparative Example 3 This comparative example was used to investigate the effect of flux basicity exceeding the range of this invention on performance. The basicity was increased above the upper limit of 3.0 by increasing the MgO and CaF2 content and decreasing the SiO2 content.

[0058] First, weigh the following dry powder raw materials: 32.0 kg of fluorite (equivalent to 31.20 kg of pure CaF2), 35.0 kg of fused magnesia (equivalent to 33.60 kg of pure MgO), 15.0 kg of bauxite (equivalent to 12.90 kg of pure Al2O3 and 0.09 kg of pure MgO), 3.0 kg of calcined alumina (equivalent to 2.97 kg of pure Al2O3), 6.0 kg of quartz sand (equivalent to 5.91 kg of pure SiO2), 4.0 kg of calcined limestone (equivalent to 3.80 kg of pure CaO), 3.0 kg of manganese ore (equivalent to 2.46 kg of pure MnO), 1.5 kg of titanium dioxide (equivalent to 1.47 kg of pure TiO2), 1.0 kg of cerium oxide (equivalent to 0.99 kg of pure CeO2), and 2.0 kg of Fe-Si alloy powder. The total dry powder input is 102.5 kg. The total unavoidable impurities in the raw materials amount to approximately 1.8 kg. After accounting for impurities, the total mass of the dry powder system is 102.5 kg.

[0059] The mass percentage of the finished flux components is as follows: CaF2 = 31.20 ÷ 102.5 = 30.4%; MgO = (33.60 + 0.09) ÷ 102.5 = 33.69 ÷ 102.5 = 32.9%; Al2O3 = (12.90 + 2.97) ÷ 102.5 = 15.87 ÷ 102.5 = 15.5%; SiO2 = 5.91 ÷ 102.5 = 5.8%; CaO = 3.80 ÷ 102.5 = 3.7%; MnO = 2.46 ÷ 102.5 = 2.4%; TiO2 = 1.47 ÷ 102.5 = 1.4%; CeO2 = 0.99 ÷ 102.5 = 1.0%; Fe-Si = 2.00 ÷ 102.5 = 2.0%; Impurities (balance) ≈ 4.9%.

[0060] Alkalinity BⅡw calculation: Numerator = 30.4 + 32.9 + 3.7 + 2.4 = 69.4; Denominator = 5.8 + 0.5 × (15.5 + 1.4) = 5.8 + 8.45 = 14.25; BⅡw = 69.4 ÷ 14.25 = 4.9.

[0061] Calculations showed that the alkalinity of this formula was too high, exceeding the scope of this invention. To investigate the performance changes when the alkalinity slightly exceeded the upper limit, the formula was adjusted as follows: the quartz sand was adjusted to 8.0 kg (SiO2 content approximately 7.7%), the fluorite to 30.0 kg (CaF2 content approximately 28.5%), and the fused magnesia to 33.0 kg (MgO content approximately 30.9%).

[0062] Adjusted alkalinity BⅡw verification: Numerator = CaF2 + MgO + CaO + MnO ≈ 28.5 + 30.9 + 3.6 + 2.4 = 65.4; Denominator = SiO2 + 0.5 × (Al2O3 + TiO2) ≈ 7.7 + 0.5 × (16.0 + 1.4) = 7.7 + 8.7 = 16.4; BⅡw = 65.4 ÷ 16.4 = 4.0.

[0063] The adjusted alkalinity is approximately 4.0, which is still higher than the upper limit of 3.0 of this invention.

[0064] The preparation process is the same as in Example 1. After sieving, the mass percentage of fine particles is 4.2%, and the mass percentage of coarse particles is 1.5%.

[0065] Boundary comparison test To verify the critical effect of the component range of the present invention, based on Example 3, only the SiO2 content was increased to 12.5%, and the amount of quartz sand was adjusted to 13.0 kg, while the other components and preparation process remained unchanged. The resulting flux basicity BⅡw was approximately 2.3.

[0066] Welding test results showed that the obtained flux slag shell exhibited slight adhesion in local areas of the weld, the oxygen content of the deposited metal was 0.033%, and the average impact energy at -40℃ was 69.2 J. This result indicates that even if the basicity value is within the range specified in this invention, the overall performance decreases when the SiO2 content exceeds the dry powder raw material ratio range defined in this invention.

[0067] Process sensitivity and window verification test To verify the process stability of the technical solution of the present invention, a disturbance test was conducted on the basic formula of Example 1, while keeping the dry powder composition unchanged, to adjust the sintering temperature and the amount of binder added.

[0068] (1) Sintering temperature deviation test The sintering temperatures of Example 1 were adjusted to 720°C and 880°C, respectively, while the other conditions remained unchanged.

[0069] When the sintering temperature is 720℃, the sintering is not sufficient, the strength of the resulting flux particles decreases, and the proportion of fine powder smaller than 0.45mm after sieving increases to 7.5%. A brief bridging phenomenon occurs during the flux hopper feeding process.

[0070] When the sintering temperature is 880℃, a locally densified glass phase appears on the particle surface. Although the strength is high, the friction between particles increases, the fluidity of the flux hopper decreases, and the feeding rate is uneven during the welding process.

[0071] This indicates that the sintering temperature needs to be controlled within the range of 750℃-850℃, otherwise it will affect the strength of the flux particles and their performance.

[0072] (2) Adhesive addition fluctuation test The amount of potassium-sodium mixed water glass added in Example 1 was adjusted to 12% and 23% (accounting for 12% of the total mass of the dry powder raw materials), respectively, while the other conditions remained unchanged.

[0073] When the amount of binder added is 12%, the wet material is not sufficiently bonded, the surface of the granules is rough after granulation, the strength of the granules is insufficient after drying, and the proportion of fine powder increases significantly after simulating transportation vibration.

[0074] When the amount of binder added is 23%, the wet material is too sticky, making granulation difficult, and the particle size is too large and uneven. After sintering, there is too much glass phase on the surface of the particles. After being placed in a humid environment (relative humidity 70%) for 48 hours, the moisture content rises to 0.8%, and the moisture absorption is enhanced.

[0075] This indicates that the amount of binder added should be controlled within the range of 15%-20% of the total mass of the dry powder raw materials.

[0076] Welding tests and performance tests The fluxes obtained in Examples 1-5 and Comparative Examples 1-3 were respectively used with commercially available H08Mn2MoA low-alloy steel submerged arc welding wire (Φ4.0mm) to conduct submerged arc welding tests on Q460E low-alloy high-strength steel plates (20mm thick). Before welding, the bevel surface of the steel plate was ground with a grinding wheel to remove oxide scale and oil.

[0077] Welding process parameters: welding current 550A, arc voltage 30V, welding speed 40cm / min, wire extension length 25mm, DC reverse polarity, interpass temperature controlled at 100℃-150℃. Flux layer thickness approximately 25mm, flux dried at 200℃ for 1 hour before welding.

[0078] After welding, the weld surface formation and slag removal are observed first. The evaluation method for slag removal performance is as follows: after the weld has cooled to room temperature, the slag shell is gently tapped with a small hammer, and the slag shell removal is observed. Then, in accordance with the relevant provisions of GB / T12470-2018 "Classification Requirements for Heat-Resistant Solid Welding Wires, Flux-Cored Welding Wires and Welding Wire-Fluoride Combinations for Submerged Arc Welding", weld metal samples are prepared at the center of the weld for chemical composition analysis and mechanical property testing. The impact test is conducted at -40℃ using Charpy V-notch specimens with a specimen size of 10mm×10mm×55mm. Three specimens are taken from each group, and the arithmetic mean is taken.

[0079] Table 1: Weld Surface Formation and Slag Removal Performance Example 1 The surface is smooth with uniform fish-scale pattern, and there are no bite edges or air holes. During the cooling process, the slag shell will lift up on its own and can be easily detached in one piece with a light tap. Example 2 The surface is smooth with uniform fish-scale pattern, and there are no bite edges or air holes. During the cooling process, the slag shell will lift up on its own and can be easily detached in one piece with a light tap. Example 3 The surface is smooth with uniform fish-scale pattern, and there are no bite edges or air holes. During the cooling process, the slag shell will lift up on its own and can be easily detached in one piece with a light tap. Example 4 The surface is smooth with uniform fish-scale pattern, and there are no bite edges or air holes. During the cooling process, the slag shell will lift up on its own and can be easily detached in one piece with a light tap. Example 5 The surface is smooth with uniform fish-scale pattern, and there are no bite edges or air holes. During the cooling process, the slag shell will lift up on its own and can be easily detached in one piece with a light tap. Comparative Example 1 The surface is smooth with relatively uniform fish scale pattern, and there are no bite edges or air holes. During the cooling process, the slag shell will lift up on its own and can be removed by gently tapping. Comparative Example 2 The weld surface formation is acceptable, but the fish-scale pattern is slightly coarse. The slag shell is relatively easy to remove; it comes off with a light tap. Comparative Example 3 The weld surface has localized indentations and uneven fish-scale patterns. The slag crust is clearly adhered to the weld surface and requires forceful tapping to partially detach it. Table 2: Chemical composition of deposited metal (mass percentage, %) Example 1 0.07 0.31 1.50 0.008 0.012 0.028 Example 2 0.07 0.33 1.53 0.007 0.011 0.026 Example 3 0.08 0.29 1.46 0.009 0.013 0.029 Example 4 0.08 0.27 1.42 0.010 0.014 0.030 Example 5 0.07 0.35 1.55 0.007 0.010 0.027 Comparative Example 1 0.07 0.31 1.49 0.008 0.012 0.031 Comparative Example 2 0.08 0.37 1.44 0.014 0.018 0.038 Comparative Example 3 0.07 0.28 1.48 0.006 0.010 0.033 Table 3: Mechanical Properties of Deposited Metal Example 1 635 546 24.5 82、77、81 80.0 Example 2 639 553 24.0 79、74、83 78.7 Example 3 630 541 25.0 75、80、73 76 Example 4 625 538 25.0 74、77、78 76.2 Example 5 640 555 23.5 76、79、80 78.3 Comparative Example 1 628 540 25.0 66、61、65 64.0 Comparative Example 2 615 526 25.5 58、62、54 58.0 Comparative Example 3 643 558 22.5 60、65、62 62.3 Table 4: Flux Storage Stability Table Example 1 The particles are uniform and there is no obvious powder. No obvious lumps were observed, and the amount of fine powder did not increase significantly. Smooth and unblocked Example 2 The particles are uniform and there is no obvious powder. No obvious lumps were observed, and the amount of fine powder did not increase significantly. Smooth and unblocked Example 3 The particles are uniform and there is no obvious powder. No obvious lumps were observed, and the amount of fine powder did not increase significantly. Smooth and unblocked Example 4 The particles are uniform and there is no obvious powder. No obvious lumps were observed, and the amount of fine powder did not increase significantly. Smooth and unblocked Example 5 The particles are uniform and there is no obvious powder. No obvious lumps were observed, and the amount of fine powder did not increase significantly. Smooth and unblocked Comparative Example 1 The particles are uniform and there is no obvious powder. No obvious lumps were observed, and the amount of fine powder did not increase significantly. Smooth and unblocked Comparative Example 2 The particles are uniform and there is no obvious powder. No obvious lumps were observed, and the amount of fine powder did not increase significantly. Smooth and unblocked Comparative Example 3 The particles are uniform and there is no obvious powder. No obvious lumps were observed, and the amount of fine powder did not increase significantly. Smooth and unblocked Results Analysis As can be seen from Examples 1-5 and Comparative Examples 1-3: 1. When the alkalinity is within the range of 2.1-3.0 and the content of each component simultaneously meets the requirements of this invention (Examples 1-5), the flux maintains good slag fluidity and stable desulfurization and dephosphorization capabilities during welding. The oxygen content of the deposited metal is controlled below 0.030%, and the average impact energy at -40℃ is above 76J. The test values ​​of each impact sample show small fluctuations, indicating good stability of low-temperature impact toughness.

[0080] 2. In Comparative Example 1, no rare earth oxides were added, and all other conditions were the same as in Example 1. The average impact energy of the deposited metal decreased from 80.0 J to 64.0 J, indicating that rare earth oxides have a positive effect on improving low-temperature toughness. The mechanism of action is that rare earth oxides form high-melting-point composite inclusions with oxygen and sulfur, promoting the transformation of inclusions from elongated strips to fine, dispersed particles.

[0081] 3. In Comparative Example 2, the flux basicity was 1.7. During welding, the slag had good fluidity and was relatively easy to remove, but its desulfurization and dephosphorization capabilities decreased. The S content in the deposited metal increased to 0.014%, the P content to 0.018%, and the oxygen content to 0.038%, while the average impact energy at -40℃ decreased to 58.0 J. This indicates that when the basicity is too low, although the slag removal performance is still acceptable, insufficient purity leads to a decrease in toughness.

[0082] 4. In Comparative Example 3, the flux basicity was 4.0, higher than the upper limit of 3.0 of this invention. During welding, the slag viscosity increased significantly, the slag shell bonded tightly to the weld, and slag removal was difficult; the oxygen content of the deposited metal was 0.033%, and the average impact energy at -40℃ was 62.3 J. This indicates that when the basicity is too high, the slag removal performance deteriorates, and the impact toughness does not improve further with increased basicity, but rather decreases.

[0083] 5. Boundary comparison tests show that even when the basicity value is within the range of 2.1-3.0 (approximately 2.3), the overall performance of the flux decreases when the SiO2 content is increased to 12.5% ​​(exceeding the upper limit of 2%), with the average impact energy at -40℃ dropping to 69.2 J. This proves that the claimed overall performance cannot be obtained if the basicity range is met but the component content exceeds the limits of this invention.

[0084] 6. Process sensitivity tests show that when the sintering temperature is outside the range of 750℃-850℃ (720℃ or 880℃) and the binder content is outside the range of 15%-20% (12% or 23%), the physical quality indicators such as flux particle strength and material flowability decrease significantly. This proves that there is a clear process window for each parameter range in the preparation process of this invention; exceeding this window will lead to damage to the performance of the flux.

[0085] Based on the above results, only when the alkalinity range and the content of each component simultaneously meet the requirements of this invention can a good comprehensive performance in terms of slag removal performance, weld purity, low-temperature impact toughness, and physical quality of flux particles be obtained.

[0086] Repeatability verification instructions The above embodiments and comparative examples were all independently repeated at least three times under the same equipment conditions, and the average variation range of the obtained impact energy was controlled within ±5%. Those skilled in the art can repeat the corresponding results based on the raw material specifications, proportions, and process parameters disclosed in the specification.

Claims

1. A sintered flux for submerged arc welding, comprising a mixture of dry powder raw materials and a binder, followed by granulation, drying, and sintering, characterized in that, The dry powder raw material is composed of the following components by mass percentage: CaF2: 22%-28%; MgO: 26%-32%; Al2O3: 18%-24%; SiO2: 8%-12%; CaO: 3%-7%; MnO: 2%-5%; TiO2: 1%-3%; Rare earth oxides: 0.5%-2%; Fe-Si alloy powder: 1%-3%; The remainder are unavoidable impurities; The binder is a potassium-sodium mixed water glass, and the amount added is 15%-20% of the total mass of the dry powder raw materials. The flux contains ≤0.030% S by mass and ≤0.030% P by mass. The basicity of the flux, calculated according to the International Institute of Welding (IIW) formula, is 2.1-3.

0.

2. The sintered flux for submerged arc welding according to claim 1, characterized in that, The dry powder raw material is composed of the following components by mass percentage: CaF2: 24%-26%; MgO: 28%-30%; Al2O3: 20%-22%; SiO2: 9%-11%; CaO: 4%-6%; MnO: 3%-4%; TiO2: 1.5%-2.5%; Rare earth oxides: 1%-1.5%; Fe-Si alloy powder: 1.5%-2.5%.

3. The sintered flux for submerged arc welding according to claim 1 or 2, characterized in that, The rare earth oxide is cerium oxide and / or lanthanum oxide.

4. The sintered flux for submerged arc welding according to claim 1 or 2, characterized in that, The purity of CaF2 is ≥97%, S≤0.02%, P≤0.02%; the purity of MgO is ≥95%; and the purity of Al2O3 is ≥85%.

5. The sintered flux for submerged arc welding according to claim 1 or 2, characterized in that, The mass ratio of K2O to Na2O in the potassium-sodium mixed water glass is 1.5:1-2.5:1, the modulus is 2.5-3.2, and the Baume degree is 38°Bé-45°Bé.

6. The sintered flux for submerged arc welding according to claim 1 or 2, characterized in that, The basicity of the flux, calculated according to the International Institute of Welding (IIW) formula, is 2.5-3.

0.

7. The method for preparing sintered flux for submerged arc welding as described in claim 1 or 2, characterized in that, Includes the following steps: Step 1, Ingredients: Weigh each component according to the mass percentage of the dry powder raw material as described in claim 1 or 2; Step 2, Dry mixing: Add the weighed dry powder raw materials into the mixing equipment and stir for 15-30 minutes; Step 3, wet mixing: Add the binder to the dry powder material and continue stirring and mixing for 10-20 minutes to obtain a wet material; Step 4, Granulation: The wet material is fed into the granulation equipment to produce granules with a particle size of 0.45mm-2.5mm; Step 5, Drying: Dry the granulated particles at 180℃-220℃ for 60min-90min; Step 6, Sintering: Sinter the dried particles at 750℃-850℃ for 60min-120min; Step 7, sieving: The sintered particles are sieved, and particles with a size of 0.45mm-2.5mm are obtained to obtain the sintered flux for submerged arc welding.

8. The method for preparing sintered flux for submerged arc welding according to claim 7, characterized in that, In step 6, the sintering temperature is 780℃-820℃ and the sintering time is 80min-100min; after sieving in step 7, the mass percentage of fine particles with a particle size less than 0.45mm in the obtained flux is no more than 5%, and the mass percentage of coarse particles with a particle size greater than 2.5mm is no more than 2%.

9. A submerged arc welding method, characterized in that, Using the sintered flux for submerged arc welding as described in claim 1 or 2, and in conjunction with low alloy steel welding wire, submerged arc welding is performed on the workpiece to be welded.

10. A submerged arc welding material composition, characterized in that, It includes the sintered flux for submerged arc welding as described in claim 1 or 2, and a low-alloy steel welding wire matched with the flux.